Monitoramento em redes IPv6 com Zabbix e Raspberry PI - Lemes, João Éder Ancelmo (2014)
This monograph aims to demonstrate a low-cost solution for monitoring IPv6 networks with Zabbix software. The network topology will have an Access Point that supports IPv6 connected to the Internet, a management server on the platform Raspberry where you install your software monitoring Zabbix, a server with Windows 2008 Server running IIS and MSSQL Server where you install the agent Zabbix for data collection services. The premise is to demonstrate that it is possible to set up a monitoring solution for small networks with a very small investment, and that low cost does not reflect the quality or performance of the system.